POTRET KEHIDUPAN RUMAH TANGGA PELAKU POLIGAMIMutimmatul FaidahFakultas Teknik, Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract The aim of the research is to analyze the household management done by women who experience nikah siri (unregistered marriages). The research cover (1) provision of financial support; (2) provision of emotional support; (3) the house of the wives; (4) self concept of a household live; and (5) marital relationship. This is a qualitative research using phenomenology and constructionism  approach. The data collection are documentation, observation, and interview. The subjects of the interview are both the first and the second wives. The research shows that there are three forms of financial support: the needs basis, the demand basis, and the willingness basis. These forms of provision is arranged based on daily schedule, the husband’s comfort, and the distance of the house. The communication between the wives is closely related with the polygamy condition. The house of the wife also determined by reasons and motive of polygamy. Women who done polygamy know that their marriage is not the same as normal marriage. Keywords: marriage, polygamy, first wife, second wife